(untitled) (SCIENCE TIME JOURNAL, 2026)
The rapid proliferation of digital communication has introduced internet memes as ubiquitous artefacts of contemporary online culture. Despite their informal origins, internet memes present distinctive pedagogical affordances for foreign language education. This article examines how internet memes function as multimodal teaching tools across key dimensions of language learning, including vocabulary acquisition, intercultural competence, motivation, and communicative creativity. Drawing on a systematic review of peer-reviewed studies and theoretical frameworks published between 2019 and 2025, this article analyses the linguistic, semiotic, and affective properties of internet memes and evaluates their integration into English as a Foreign Language (EFL) and English as a Second Language (ESL) classrooms. Findings indicate that meme-based instruction significantly enhances learner engagement and contextual vocabulary retention, while simultaneously fostering critical digital literacy and intercultural awareness. The article concludes by proposing a conceptual framework—the KarMeme Instructional Model—for principled meme integration in language pedagogy, and identifies directions for future empirical research.